Notary Responsibility for Legally Defective Deeds: Analysis of the Principle of Due Diligence in the Performance of Public Official Duties - Triwanto Triwanto; Alya Maya Khonsa Rahayu; FX. Hastowo Broto Laksito; Lintang Cahya Primadani (Lembaga Pengembangan Kinerja Dosen, 2026)
This article comprehensively discusses the responsibility of notary for legally defective deeds, with an emphasis on the application of the principle of prudence as the foundation of the notary profession's professionalism and integrity. This research uses a normative legal method with a legislative, conceptual, and case approach to analyze the relationship between notary negligence and the resulting civil liability consequences. The study results indicate that the principle of prudence plays a central role in determining the limits of a notary's legal liability, as any negligent action in verifying identity, document validity, or the substance of the deed can cause legal harm to the parties. Conversely, if the notary can prove that their actions were in accordance with legal procedures and professional ethical standards, they can be absolved of civil liability claims. Additionally, this research also highlights the importance of applying the principle of due diligence in the context of the digitalization of notarial services, which demands stricter verification and authentication. Thus, the principle of prudence not only serves as a legal principle but also as a moral foundation that guaranties justice, certainty, and legal protection for society, as well as upholding the dignity of the notarial profession.